Implementasi RESTful API dan Push Notifikasi pada Sistem Informasi Acara Kebudayaan di Indonesia Berbasis Android - Rifqi Helmi Fadhil; Sutarman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
Indonesia has a wide cultural diversity, but it is difficult to find information about upcoming cultural events because of its inefficient and limited dissemination. This is because the information is spread only through media such as the Internet, print media, and electronics that only cover specific areas. The aim of this research is to build an Android-based Indonesian cultural event information system that will implement RESTful API and push notification features. Waterfall becomes the method used in the system mining process by passing the stages of requirements analysis system, system design, implementation, and testing. This research produces two systems, namely websites and applications. The website is operated by the event manager as an admin to process event data, while the application is operated by society and tourists to search for cultural events. This cultural event information system can facilitate society and tourists in finding information on cultural events that will take place in Indonesia.